Facsimiles of early charters from Northamptonshire collections - Stenton, F. M. (Frank Merry), 1880-1967 (Publications of the Northamptonshire Record Society, 1930)
Facsimiles, with transcripts and notes, of royal and other charters in favour of religious houses and of laymen in various counties, 11th-13th centuries.